Fostering Critical Thinking About the Critique of Religion: An Empirical Multi-Case Analysis - Jarmer, Sebastian Tjelle (Religions, 2024)
Having the right to criticize religion is important for healthy democracies. However, much critique of religion has led to increased levels of polarization. This article explores how religious education can help facilitate critical thinking regarding the critique of religion. By analyzing actual teaching practices about the critique of religion, this article contributes to the field of religious education research in three ways. First, it contributes empirically to the field of religious education, which to a limited degree has studied authentic classroom practices through observations. Second, it contributes theoretically to the field by analyzing which contextual dependencies of teaching facilitate critical thinking about the critique of religion. Third, this study builds on and adds to the prior research about the critique of religion within religious education, which has mainly been theoretical.